2018
DOI: 10.21273/hortsci13411-18
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-induced Salinity Tolerance Improves Photosynthesis, Leaf Water Status, Membrane Stability, and Growth in Pepper (Capsicum annuum L.)

Abstract: Salt stress is a major problem worldwide because it decreases yields of many important agricultural crops. Silicon is the second-most abundant element in soil and has numerous beneficial effects on plants, particularly in alleviating stress-related impacts. Pepper is an important crop in the Mediterranean region, but pepper varieties differ in their salinity tolerances. The objective of this research was to test the ability of silicon to mitigate effects of salt stress in both salt-sensitive and salt-tolerant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
(38 reference statements)
2
19
0
Order By: Relevance
“…and Altuntas et al . who suggested that K content decrease is compensated by the increase in Na content . Similarly, Na + levels were significantly higher when plants were grown in saline conditions which is confirmed by the results of Del Amor et al .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…and Altuntas et al . who suggested that K content decrease is compensated by the increase in Na content . Similarly, Na + levels were significantly higher when plants were grown in saline conditions which is confirmed by the results of Del Amor et al .…”
Section: Discussionsupporting
confidence: 68%
“…Plant photosynthetic rate is also negatively affected by high salinity, which could change positively or negatively the protein content, thus affecting quality and inducing several plant secondary metabolism processes and antioxidant mechanisms to resist the impacts of salinity . Several means for the alleviation of negative impacts of salinity have been suggested, including the exogenous application of cations, either through the rooting system or via foliar applications …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In relative terms, plants grown under ECw of 3.5 dS m -1 reduced their A by 51.85% (3.80 μmol H 2 O m -2 s -1 ) compared to those subjected to the lowest salinity level (0.3 dS m -1 ). The reduction in CO 2 assimilation rate in plants grown under salt stress occurs due to stomatal closure to reduce water loss, which in turn leads to reductions in leaf transpiration rates and intercellular CO 2 concentration in the leaves (Altuntas, Dasgan, & Akhoundnejad, 2018), promoting a decrease in CO 2 availability for carboxylation (E. N. da Silva, Ribeiro, Ferreira-Silva, Viégas, & Silveira, 2011).…”
Section: Table 2 Summary Of the Analysis Of Variance For Stomatal Conmentioning
confidence: 99%